2021
DOI: 10.5194/egusphere-egu21-10768
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combination of GNSS and VLBI data for consistent estimation of Earth Rotation Parameters

Abstract: <p>We present the current activities of the Federal Agency for Cartography and Geodesy (BKG) towards a combined processing of VLBI and GNSS data.  The main goal of the combined analyses of the two different space-geodetic techniques is the improvement of the consistency between the techniques through common parameters, i.e., mainly Earth Rotation Parameters (ERPs), but also station coordinates and tropospheric parameters through local ties and atmospheric ties, respectively.</… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Figure 2 summarizes the processing steps and the entire combination procedure. It is an extension of the combination scheme presented in Lengert et al (2022). It is extended by the multi-day intra-technique VLBI combination (n-VLBI) and the final combination (COMBI FIN) presented hereafter.…”
Section: Combination "Final" (Combi Fin)mentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 2 summarizes the processing steps and the entire combination procedure. It is an extension of the combination scheme presented in Lengert et al (2022). It is extended by the multi-day intra-technique VLBI combination (n-VLBI) and the final combination (COMBI FIN) presented hereafter.…”
Section: Combination "Final" (Combi Fin)mentioning
confidence: 99%
“…Studies have shown that the selection of the reference point with no correction does not affect the estimated dUT1 values. The addition of Galileo observations into the analysis process has no noticeable effect on the magnitude of the bias (Lengert et al 2022). Furthermore, the EOP of the last day of each GNSS Rapid are extracted and the EOP offsets of the first two days of the 3-day polygons are pre-eliminated.…”
Section: Combination "Final" (Combi Fin)mentioning
confidence: 99%
See 2 more Smart Citations